Determination of exchange enthalpy and entropy parameters of poly(dimethyl siloxane) with some n-alkanes by inverse gas chromatography - Cankurtaran, O; Yilmaz, F (JOHN WILEY & SONS LTD, 1996)
The total interaction parameter at infinitely high polymer concentration, chi(t)(infinity), and the effective exchange energy parameter, , of poly(dimethyl siloxane) with n-pentane, n-hexane, n-heptane and n-nonane were determined around room temperature using the inverse gas chromatography technique. The values of chi(t)(infinity) are in agreement with corresponding literature values. The exchange enthalpy X(12) and entropy, Q(12), parameters were determined at the same temperature. The X(12) parameters increase with the carbon number of the n-alkanes, while their temperature dependence is almost negligible. The Q(12) parameters are approximately independent of temperature and carbon number of the n-alkanes.
Keywords: poly(dimethyl siloxane); polymer-solvent interactions; equation of state parameters; inverse gas chromatography; OF-STATE PARAMETERS; POLYSTYRENE SOLUTIONS; POLYDIMETHYLSILOXANE-SOLUTIONS; LIQUID-CHROMATOGRAPHY; THERMODYNAMICS; CYCLOHEXANE; SOLVENTS; SYSTEMS; FLORY; Polymer Science